The Interaction between DELLA and ARF/IAA Mediates Crosstalk between Gibberellin and Auxin Signaling to Control Fruit Initiation in Tomato. Issue 8 (15th July 2018) - Hu, Jianhong; Israeli, Alon; Ori, Naomi; Sun, Tai-ping
Abstract : Gibberellin and auxin regulate tomato fruit initiation through direct crosstalk, a process mediated by a gibberellin signaling repressor and auxin signaling components SlARFs/SlIAA9. Abstract: Fruit initiation following fertilization in angiosperms is strictly regulated by phytohormones. In tomato ( Solanum lycopersicum ), auxin and gibberellin (GA) play central roles in promoting fruit initiation. Without fertilization, elevated GA or auxin signaling can induce parthenocarpy (seedless fruit production). The GA-signaling repressor SlDELLA and auxin-signaling components SlIAA9 and SlARF7 repress parthenocarpy, but the underlying mechanism is unknown. Here, we show that SlDELLA and the SlARF7/SlIAA9 complex mediate crosstalk between GA and auxin pathways to regulate fruit initiation. Yeast-two-hybrid and coimmunoprecipitation assays showed that SlARF7 and additional activator SlARFs interact with SlDELLA and SlIAA9 through distinct domains. SlARF7/SlIAA9 and SlDELLA antagonistically modulate the expression of feedback-regulated genes involved in GA and auxin metabolism, whereas SlARF7/SlIAA9 and SlDELLA coregulate the expression of fruit growth-related genes. Analysis of procera ( della ), SlARF7 RNAi (with downregulated expression of multiple activator SlARFs ), and entire ( iaa9 ) single and double mutants indicated that these genes additively affect parthenocarpy, supporting the notion that the SlARFs/SlIAA9 and SlDELLA interaction plays an important role in regulating fruit initiation. Analysis of the GA-deficient mutant gib1 showed that active GA biosynthesis and signaling are required for auxin-induced fruit initiation. Our study reveals how direct crosstalk between auxin- and GA-signaling components is critical for tomato fruit initiation.